"It Feels So Good": Pleasure in Last Sexual Encounter Narratives of Black University Students. (March 2018) - Hargons, Candice N.; Mosley, Della V.; Meiller, Carolyn; Stuck, Jennifer; Kirkpatrick, Brett; Adams, Caroline; Angyal, Blanka
A sex-positive lens is needed to investigate Black sexuality, which is often depicted through deficit and risk models. Extant sex research leaves an opportunity to understand Black experiences of sexual pleasure untapped. Using narrative inquiry coupled with constructivist grounded theory methods, we examined 18 Black university students' last sexual encounter narratives. An explication of their disclosure about and meaning making around pleasure is presented. Themes included the following: monitoring mutual pleasure, relegating pleasure to men's performance, and positioning pleasured possibilities as hope or expectation. Research implications for Black psychology are addressed.